1983
DOI: 10.1136/bmj.286.6375.1384
|View full text |Cite
|
Sign up to set email alerts
|

Location of parathyroid adenomas by thallium-201 and technetium-99m subtraction scanning.

Abstract: Solitary parathyroid adenomas were correctly located before surgery in 20 out of 21 cases by using 20lmTl and 99mTc in a subtraction technique. The Attempts at detecting parathyroid adenomas with 75Se-selenomethionine and "31Cs-caesium chloride have been unsatisfactory. 205Tl-thallous chloride has better imaging properties, and preliminary reports7 suggest that it is a superior agent for identifying parathyroid tissue. Because thallium is also taken up by the thyroid gland we have used a subtraction techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

1986
1986
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…Thallium-technetium subtraction parathyroid scan, a relatively new technique for loacalization of hyperfunctioning parathyroid tissue devel oped by Ferlin et al [15], seems to be very promising. The scan correctly localized hyperfunctioning parathy roid tissue in 89-92% of the cases surgically proven to be adenomatous, carcinomatous, or hyperplastic [15][16][17][18], This test is particularly useful in patients who have undergone previous neck explorations. In our case the thallium-technetium subtraction scan was beneficial, while the information obtained by venous sampling was confusing and did not help in localizing the hyperplastic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thallium-technetium subtraction parathyroid scan, a relatively new technique for loacalization of hyperfunctioning parathyroid tissue devel oped by Ferlin et al [15], seems to be very promising. The scan correctly localized hyperfunctioning parathy roid tissue in 89-92% of the cases surgically proven to be adenomatous, carcinomatous, or hyperplastic [15][16][17][18], This test is particularly useful in patients who have undergone previous neck explorations. In our case the thallium-technetium subtraction scan was beneficial, while the information obtained by venous sampling was confusing and did not help in localizing the hyperplastic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy about the value of diagnostic methods used in patients with persistent or recurrent hyperparathyroidism [13][14][15][16][17][18], The role of selective ve nous sampling with PTH radioimunoassay in the diag nosis of a fifth gland has not been clarified. This method is of questionable value in measuring concen trations of PTH in the large veins of the mediastinum [11,14], Of interest is that our patient had no signifi cant step-up in PTH levels in the area where the fifth gland was discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide procedures have also been used for this purpose. Previously, the most commonly used scintigraphic approach has been a dual isotope procedure combining 201 Tl-thallous chloride with either 99m Tc-pertechnetate or 123 I-labeled sodium iodide (2). More recently, 99m Tc-sestamibi has become a popular substitute for thallium-201 in scintigraphic parathyroid localization studies.…”
Section: I/mentioning
confidence: 99%
“…Laborato ry examination revealed that he had hypercalcemia of 3.0 mmol/l with unsuppressed plasma parathyroid hormone, and decreased per cent tubular resorption of phosphate as low as 78%. Computed tomo graphic scan and :olTI-99mTc subtraction scintigraphy [18] showed a mass lesion at the left lower pole of the thyroid gland. Since his hyper calcemia was quite symptomatic, subtotal thyro-parathyroidectomy was performed promptly, which immediately normalized the hyper calcemia.…”
Section: Patientmentioning
confidence: 99%